Poverty Traps and Nonlinear Income Dynamics with Measurement Error and Individual Heterogeneity - Antman, Francisca; McKenzie, David J. (World Bank, Washington, DC, 2012)
Theories of poverty traps stand in sharp contrast to the view that anybody can make it through hard work and thrift. However, empirical detection of poverty traps is complicated by the lack of long panels, measurement error, and attrition. This paper shows how dynamic pseudo-panel methods can overcome these difficulties, allowing estimation of non-linear income dynamics and testing for the presence of poverty traps. The paper explicitly allows for individual heterogeneity in income dynamics to account for the possibility that particular groups of individuals may face traps, even if the average individual does not. These methods are used to examine the evidence for a poverty trap in labor earnings, income, and expenditure in Mexico and are compared to panel data estimates from a short rotating panel. The results do find evidence of nonlinearities in household income dynamics and demonstrate large bias in the panel data estimates. Nevertheless, even after allowing for heterogeneity and accounting for measurement error, the paper finds no evidence of the existence of a poverty trap for any group in the sample.